Microfinance as a Catalyst for Employment Generation in Kailali District: Unlocking Opportunities in Agriculture and Small Industries (Sudurpaschim Spectrum, 2024)
This study explores the pivotal role of microfinance in generating employment within the agriculture and small industries sectors of Kailali District, Nepal. Drawing on secondary data from government reports, NGO publications, and academic studies, the research employs descriptive analysis, trend evaluation, and comparative methods to assess the contribution of microfinance institutions (MFIs) to entrepreneurship and self-employment. Findings reveal that microfinance has driven notable progress, with self-employment in agriculture rising by 15% and micro enterprises in small industries increasing by 25%. The sector has also witnessed diversification in 2/27 agricultural practices, contributing to reduced seasonal unemployment and the growth of women-led enterprises. Despite these positive outcomes, the study identifies key challenges such as limited loan sizes, high-interest rates, and market saturation that hinder the broader impact of microfinance on employment. The study concludes by emphasizing the need for targeted financial strategies, scaling-up of micro-enterprises, interest rate reductions, and integration of MFIs into larger value chains to ensure sustainable employment growth in Kailali District.